Application of stress-wave theory to piles : quality assurance on land and offshore piling : proceedings of the Sixth International Conference on the Application of Stress-Wave Theory to Piles, São Paulo, Brazil, 11-13 September, 2000 /: quality assurance on land and offshore piling : proceedings of the Sixth International Conference on the Application of Stress-Wave Theory to Piles, São Paulo, Brazil, 11-13 September, 2000. ([2014?]) - Unknown
No abstract available